Mom: Let's Save Morality Through the Historical Contributions of the Pedagogical Renewal - Fernández Antón, Estefanía (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of this work is to identify the significance of the mother's role, in social development. for three initiatives of the Renewal of Pedagogy. These are the Institución Libre de Enseñanza, the Escuelas del Ave María and the Escuela Moderna de Barcelona. To reach the aim indicated we have analyzed primary sources. These are publications of magazines with socio-educational purposes mainly. And they warn us of a disparate discourse between the three projects. Determining, as the main conclusion, that the proposals examined had their own approaches to the meaning of mother. But all them affirmed the importance of her figure.